Clinical Outcomes of Anatomical Reconstruction of the Lateral Ankle Ligament Complex: A Systematic Review. Issue 4 (November 2022) - Azam, Mohammad T.; Mulvin, Conor; Mercer, Nathaniel P.; Toale, James P.; Hurley, Eoghan T.; Weiss, Matthew B.; Ubillus, Hugo A.; Kennedy, John G.
Category: Ankle; Hindfoot; Sports; Trauma Introduction/Purpose: While surgery is often indicated in the treatment of chronic ankle instability (CAI), there lacks consensus on which procedure is preferable in light of the multiple different procedures available. In this systematic review, we evaluate the recent literature on the anatomical reconstruction of the lateral ligaments in the treatment of CAI in an effort to identify differences in clinical and radiological outcomes between allograft and autograft reconstruction techniques. Methods: A systematic search of PubMed, EMBASE, and Cochrane Library databases was performed in October 2019 resulting in 13 studies ranging from the years 1991 to 2017. The studies included were carefully evaluated with regards to the level of evidence (LOE) and quality of evidence (QOE), clinical and radiological outcomes, complications, revision rates and return to sport. Results: Thirteen studies including a total of 296 ankles were included; Within the autograft group, the weighted mean AOFAS improved from 66.9 to 95.9 at a weighted mean follow-up of 29.6 months, KPSSAF scores improved from 48 to 92.2 at a weighted mean follow-up of 37 months, VAS scores improved from 6.8 to 0.2 at a weighted mean follow up of 33.5 months, and the complication rate was 7.7% at a follow up of 31.2 months. Within the allograft group the AOFAS improved from 53.7 to 89.3 at a follow-up of 35.5 months, KPSSAF scores improved from 42.8 to 90.4 at a follow up of 34 months, VAS scores improved from 7.3 to 1.9 at a follow up of 38 months, and the complication rate was 7% at a follow up of 34.9 months. Conclusion: The current systematic review demonstrated that anatomical reconstruction of CAI resulted in favorable clinical and radiological outcomes, low complication and revision rates and excellent return to sport rates in the short-term follow-up. Comparison of autograft and allograft reconstruction techniques for chronic lateral ankle instability showed minor differences both clinically and radiologically but none which would suggest superiority of one technique over another.